¿In a grey area? The climate and environmental migration in International Law, including the 2030 Agenda - Torres Rangel, Andrés Ramón (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2023)
Millions of people around the world have been forced to move due to natural disasters and the negative effects of climate change. This situation has sparked the academics’ interest in develop their studies from different fields of knowledge to make this issue a global problem must be solved, which has not been achieved even thought the creation of the 2030 Agenda. Thus, this article aims to do a sociological-legal study on a global scale about the evolution of the legal recognition and the climate and environmental migrants’ justiciable character from the perspective of human rights.
Keywords: climate and environmental displacement; migration; Public International Law; Sustainable Development Goals; human rights